2007
DOI: 10.1111/j.1439-0426.2007.00866.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and body composition of sub-yearling Persian sturgeon, (Acipenser persicus, Borodin, 1897), fed different dietary protein and lipid levels

Abstract: In order to evaluate the protein and energy requirement of Persian sturgeon (Acipenser persicus) sub-yearlings, eight experimental diets containing two protein levels (40% and 45%) and four lipid levels (10%, 15%, 20% and 25%) were tested. Sturgeons (W 0 ¼ 136.8 g) were fed the experimental diets to satiation four times daily for 150 days, resulting in a final mean weight of 375.8 g. Growth was significantly affected by lipid content of the diets. At 40% protein level, weight gain and specific growth rate (% p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
44
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 34 publications
15
44
2
Order By: Relevance
“…This effect has also been reported on other fish species (Kaushik, Breque & Blanc, 1991;Mohseni et al, 2007;Siddiqui, Howlader & Adam, 1988 Values are presented as means AE SE of triplicate groups (n = 3). Fish fed higher protein diets had significantly higher serum ammonia levels compared to those fed lower protein diets (p < .05).…”
Section: Physiological Parameterssupporting
confidence: 83%
See 1 more Smart Citation
“…This effect has also been reported on other fish species (Kaushik, Breque & Blanc, 1991;Mohseni et al, 2007;Siddiqui, Howlader & Adam, 1988 Values are presented as means AE SE of triplicate groups (n = 3). Fish fed higher protein diets had significantly higher serum ammonia levels compared to those fed lower protein diets (p < .05).…”
Section: Physiological Parameterssupporting
confidence: 83%
“…Although the coefficient of determination was improved when SGR data were fitted to the second-order poly-Pourkazemi, 2007), which estimated the dietary protein level for maximum growth of juvenile sturgeons to be around 36%-42%. Although the coefficient of determination was improved when SGR data were fitted to the second-order poly-Pourkazemi, 2007), which estimated the dietary protein level for maximum growth of juvenile sturgeons to be around 36%-42%.…”
mentioning
confidence: 99%
“…In the current study, WG, BWI, SGR and FCR were improved in fish fed 15% lipid (compared to 10%), indicating the protein‐sparing effect of lipid. Similar results at suboptimal water temperature have been reported in other studies (Kim et al., ; Mohseni et al., ). Bendiksen et al.…”
Section: Discussionsupporting
confidence: 91%
“…() found similar protein requirement (range of 34%–37%) for juvenile hybrid sturgeon ( Acipenser baerii ♀ × A. gueldenstaedtii ♂). Earlier sturgeon studies showed dietary protein requirement of about 40% (Kaushik, Breque, & Blanc, ; Mohseni, Pourkazemi, Hosseni, Hassani, & Bai, ; Mohseni, Sajjadi, & Pourkazemi, ; Molla & Amirkolaie, ). The discrepancies among these values is probably because of differences in fish size, species, water temperature, dietary energy levels, protein quality, dietary non‐protein energy levels, or protein to energy ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Rearing of Acipenser sturgeons in ponds and tanks is a relatively new industry in Iran, and information on nutrient utilization and dietary requirements is limited (Moore et al., 1988; Gershanovich and Kiselev, 1993; Ebrahimi, 2006; Mohseni et al., 2007). From hatching until market size (4–6 kg), which takes approximately 15–17 months, 98% of the beluga is fed a commercial diet.…”
Section: Introductionmentioning
confidence: 99%